Pengaruh Contextual Teaching and Learning Tipe Card Match dan Realistic Mathematics Education Terhadap Kemampuan Komunikasi Matematika - Yoga Juliansyah (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2018)
This research aims to know the differences of Contextual Teaching and Learning (CTL) Model with Card Match type and Realistic Mathematic Education (RME) Model to the mathematical communication ability of grade IV SDN Batu Ampar 02 Pagi, East Jakarta. The research method was comparative-quantitative with Quasi Experiment Method with posttest-only research design. The sample of the research was 64 students. The research instrument was a mathematical communication ability test in the essay form containing 7 items with score value 0-4. The instrument has been tested previously with validity and reliability test. Based on the results of the normality and homogeneity test of mathematical communication ability in IVA (Experiment Class I) and class IVB 's (Experiment Class II), the data were normally distributed and homogeneous. Furthermore, data analysis techniques used hypothesis test. The results showed the average value of mathematical communication skills of the Experiment I class using the CTL with Card Match type was 19.3, it was higher than the Experiment II class using the RME Model of 18. Based on hypothesis test, it can be concluded that there were differences between CTL Type Card Match Model and RME Model on mathematical communication ability of students at SDN Batu Ampar 02 Pagi, East Jakarta.